Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Berfikir Kritis Siswa Muatan Pembelajaran IPAS Kelas IV SD Swasta Kartika 1-2 - Nuria Marsella Sihaloho; Antonius Remigius Abi; Anton Sitepu; Reflina Sinaga; Dyan Wulan Sari HS (Departement of Mathematics Education, 2024)
This research aims to determine the influence of the Problem Based Learning learning model on students' critical thinking abilities, science and technology learning content for class IV Kartika Private Elementary School 1-2 in the 2023/2024 academic year. The research method used is an experimental method with a quantitative research type. To obtain the data required a test instrument of 30 questions. The total research sample was 34 students based on purposive sampling technique. To determine students' initial abilities, the research conducted a Pre Test with an average score of 52.55 which was in the poor category. The results of the Post Test have improved from the Pre Test results given previously with the students' average score reaching 75.52 in the good category. It can be said that the level of success in students' critical thinking has increased as evidenced by the results of the correlation coefficient test calculation, which obtained r_count ≥ r_tabel with results of 0.610 ≥ 0.339. Next, hypothesis testing is comparing the t_count≥ t_table values. The obtained value of t_count = 4.357 while t_table = 1.690. Because t_count ≤ t_table (4.357 ≥ 1.690) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the problem based learning model on students' critical thinking abilities.